Rocks and leaves: Can anatomical leaf traits reflect environmental heterogeneity in inselberg vegetation? - Paula, Luiza F. A. de; Kolb, Rosana Marta [UNESP]; Porembski, Stefan; Silveira, Fernando A. O.; Rossatto, Davi Rodrigo [UNESP] (Elsevier B.V., 2019)
Inselbergs, isolated rock outcrops that rise above the surrounding landscape, harbor a highly diverse flora. Differences in slope, water availability, soil depth and sun exposure result in the creation of microhabitats characterized by distinct resource availability, where unique plant communities are found. However, there is a lack of studies examining specific traits structuring communities in each microhabitat. We investigated the leaf anatomical structure of Brazilian inselberg species by comparing leaf anatomical traits of plants occurring in two microhabitats with contrasting resource availability: monocot mats (MM; extremely stressful) and shallow depressions (SD; less stressful). We hypothesized that species in the contrasting microhabitats would show different arrays of leaf anatomical traits. Seventeen quantitative and qualitative anatomical traits that have functional significance were analyzed. Firstly, we qualitatively evaluated leaf structural features, and then measured and compared tissues between plants in SD and in MM, using ANOVA and ordination analyses. An ANOSIM was also run to look for differences between the two groups. Our results show that most of the species growing in MM showed more conservative traits related to water retention and drought resistance, whereas species growing in SD showed more diversified resource strategies. These findings reinforce the heterogeneous aspect of inselberg vegetation in Brazil, which is under variable degree of environmental stress.
Keywords: Brazil; Leaf anatomical traits; Leaf economics spectrum; Mat-forming communities; Monocots; Rock Outcrops